Geochronology and Geochemistry of the Karadaban Bimodal Volcanic Rocks in the Altyn Area, Xinjiang: Implications for the Tectonic Evolution of the Altyn Ocean. (19th August 2019) - Jia, Wen-Bin; Yan, Guang-Sheng; Yu, Xiao-Fei; Li, Yong-Sheng; Conticelli, Sandro; Du, Ze-Zhong
Abstract : Detailed geochronological, geochemical, and Sr-Nd-Hf isotopic data are presented for early Paleozoic volcanic rocks in the Karadaban area from the northern Altyn region, NW China, with the aim to constrain their petrogenesis and tectonic implications. The Karadaban volcanic rocks show a bimodal distribution in composition, with rhyolite and basalt. The LA-ICP-MS zircon U-Pb age indicates that the volcanic rocks were erupted at 512 Ma. The mafic rocks are calc-alkaline, enriched in light rare earth elements (LREE) and large-ion lithophile elements (LILE; Ba and U) and depleted in high-field strength elements (HFSE; Nb and Ta). These features together with their depleted isotopic signature (initial 87 Sr / 86 Sr = 0.70413 – 0.70817, ε Nd t = 2.7 to 3.7) suggest that they were likely derived from a depleted mantle source but mixed with crustal components while upwelling. The felsic rocks show an A-type affinity, with high alkalis and Rb/Sr and Ga/Al ratios; enriched in LILE (e.g., Rb, K, Th, U, and REE) and depleted in Ba, Sr, Nb, P, and Ti; and with fractionated REE patterns with strong negative Eu anomalies. The combination of the decoupling ofε Nd t values (−2.5 to −6.3) andε Hf t values (+5.5 to +14.7) in the setting of subduction indicates that the felsic rocks were generated by partial melting of the juvenile crustal as a result of magma upwelling. The geochemical and Sr-Nd-Hf isotopic characteristics, coupled with regional geology, indicate that the formation of the Karadaban bimodal volcanic rocks involves an extensional regime associated with a subduction-related environment. The rifting of the back arc in response to the retreat of the subducting northern Altyn oceanic lithosphere may account for the Karadaban bimodal volcanic rocks.